2020
DOI: 10.1109/access.2020.3004745
|View full text |Cite
|
Sign up to set email alerts
|

Building Decentralized Fog Computing-Based Smart Parking Systems: From Deterministic Propagation Modeling to Practical Deployment

Abstract: The traditional process of finding a vacant parking slot is often inefficient: it increases driving time, traffic congestion, fuel consumption and exhaust emissions. To address such problems, smart parking systems have been proposed to help drivers to find available parking slots faster using latest sensing and communications technologies. However, the deployment of the communications infrastructure of a smart parking is not straightforward due to multiple factors that may affect wireless propagation. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The propagation parameters are calculated along the path of each ray, which interacts with all the elements within the scenario, creating radio propagation phenomena such as reflection, refraction, and diffraction. These characteristics, added to the implementation of the material properties of all the elements within the scenario (conductivity and permittivity) lead to an efficient and robust technique already employed and validated in many different environments, including large urban environments [30] [31].…”
Section: A 3d Ray Launching Techniquementioning
confidence: 99%
“…The propagation parameters are calculated along the path of each ray, which interacts with all the elements within the scenario, creating radio propagation phenomena such as reflection, refraction, and diffraction. These characteristics, added to the implementation of the material properties of all the elements within the scenario (conductivity and permittivity) lead to an efficient and robust technique already employed and validated in many different environments, including large urban environments [30] [31].…”
Section: A 3d Ray Launching Techniquementioning
confidence: 99%
“…With driver behavior analysis and parking traffic prediction, this system handles parking demands by allocating available parking lots with improved efficiency. The authors of [20] suggested a decentralized parking system that uses fog computing and IoT to provide parking services. The system validates real-world parking traffic with a characterized traffic using the 3D-Ray Launching (3D-RL) tool and provides parking services accordingly.…”
Section: Background Studymentioning
confidence: 99%
“…The Internet of Things (IoT) empowers smart connectivity and advanced communication paradigms in wireless sensor networks (WSNs) to, among other things, enable well-performing intelligent transportation systems (ITSs), including SP systems, which are considered integral parts of innovative smart-city projects [1,2]. The IoT is a generic platform that is used to overcome the technological limitations of existing transportation systems, such as SP systems, traffic-congestion systems, and energy-consumption systems; thereby, IoT-enabled features, such as monitoring, controlling, and data analytics, can strengthen the performances of larger SP systems in metropolitan areas [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the SP system can play an essential role in saving drivers time when searching for parking in urban areas on demand; this can be of great assistance to minimizing traffic congestion and saving energy (e.g., gasoline), which further leads to a reduction in air pollution. As a part of the SP system, the parking payment as per the occupation of the driver can easily be made, with some built-in payment methods online, which therefore saves the driver time (instead of waiting in a long row), without interrupting other drivers [1,4]. and ensure an end-to-end information stream (for example, the successful transactions between edge devices to fog to cloud to end users, and vice versa) [11,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation